1500-year cycle dominated Holocene dynamics of the Yellow River delta, China. (February 2016) - Yi, Liang; Chen, Shenliang; Ortiz, Joseph D; Chen, Guangquan; Peng, Jun; Liu, Feng; Chen, Yanping; Deng, Chenglong
The world's mega-deltas are extremely important from a human perspective and attract considerable effort to reveal their evolution, growth-related driving forces, and human impacts. Here, we report a case study on the Holocene deltaic evolution of the Yellow River, through development of a conceptual model, which is compared with paleo-proxy to analyze the forcing acting on the delta. The main conclusion is that superlobe switching was modulated by the 1500-year cycle. Cooling in Mongolia in response to strong Bond IRD events, which is coincident with warming in eastern China due to a strong Kuroshio Current, enhances the meridional temperature gradient, which then increases cyclone frequency and activates dust storms and terrestrial erosion throughout the catchment. Enhanced erosion supplies great amounts of material to the Yellow River and causes channel evulsion and superlobe development, expressed as dominant 1500-year cycle. At the same time, summer monsoon and solar forcing are uncorrected with deltaic evolution on these timescales. Therefore, we conclude that Holocene dynamics of the delta on a millennial timescale was dominated by winter cyclone activity across northern China and Mongolia.